Humanized care in the immediate postoperative period of hysterectomized patients - Yuneyda Beatriz Camero Solórzano; Isabel Cristina Meléndez Mogollón; Arelys Rebeca Álvarez González; Jenny Apuntes Guerrero (Universidad de Alicante, 2019)
Objective: To analyze the humanized care in the immediate postoperative period of hysterectomized patients, from 25's to 40's, of the Olympus Clinic, during the period March-August 2017. Method: The study is carried out under a quantitative approach, with a descriptive level, supported by a field investigation. The information was based on a 11 items questionnaire, which was applied to 18 nurses in order to obtain the required data. Results: The application of humanized care is evidenced partially in the attention of biological needs in patients. It is noted that most of the respondents communicate effectively, however, a high level of indifference is manifested, on the part of nursing staff, in the pain attention as a basic need in the postoperative hysterectomy. Likewise, the absence of an instrument for evaluating user satisfaction is a weakness. Conclusions: Humanized care is a complex but essential process during post-operative care in hysterectomies. Within the health institution addressed, it is developed in a fragmented manner, however, there is an opening in nursing professionals for the humanization of care.